Effect Of Some Enzymes Activity In Liver Diseases From Patients Of Salmonella Paratyphi A With Iraqi Woman. - Al-Shammaa, N. M. J.; Al- Wihaly, B. H .; Abass, E. A.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This present study demonstrated that liver was involved in 14 %of typhoid patients manifesting with hepatomegaly. Elevation of serum enzymes in typhoid fever was presumably of a muscular origin, while elevation of liver enzyme was relatively less common. This study was performed on 30 female patients diagnosed by ultrasound (US) of abdomen, with paratyphoid A, ranged between (20-40) years compared with 30 healthy control .Patients volunteers were treated with appropriate antibiotics for 14 days and investigations were repeated 2-3 week after completion of treatment. Patients had clinical and biochemical evidence of hepatic dysfunction. The spectrum of hepatic involvement included hepatomegaly , jaundice, derangement of various hepatic functions and abnormal US abdomen. The results revealed a highly significant values increase in serum AST and ALT compared to control was found while a significant increase of serum ALP compared to control was noticed and a significant decrease in serum LDH compared to control was obtained.